The Use of Social Media as a Platform for Obtaining and Disseminating Da'wah Content by College Students - Ratmiati, Ratmiati; Syabri, Hadi; Faziola, Fahmi; Bari, Ibnu Jarir Atha; Azmi, Fazrul (Universitas Islam negeri Mahmud Yunus Batusangkar, 2023)
The Information Technology era inseparably intertwines students' behavior with internet usage through computers, laptops, and gadgets. Da'wah (Islamic preaching) is a responsibility for every Muslim, regardless of their profession, requiring effective means for its delivery. Social media serves as a platform for accessing and disseminating moral messages of da'wah. This qualitative descriptive research focuses on the utilization of social media by students for obtaining and spreading Islamic da'wah content. The study involves students of Islamic Education at UIN Batusangkar, specifically the 2023 cohort. Data collection employed a questionnaire distributed to 50 students from December 6 to December 15, 2023. Key findings reveal that 100% of students possess social media applications, with 86% favoring Instagram. Furthermore, 100% have encountered digital da'wah, 78% consistently receive it through the